Comparison Analysis of Taxable Income (PKP) Taxpayer before and After-Tax Audit - Suhidayat, Tatang; Herdyansyah, Ridwan (Budapest International Research and Critics University, 2021)
There is a big difference between taxable income before and after inspection by the tax office, resulting in the taxpayer lacking goods. This study aims to analyze the comparison of the taxable income of corporate taxpayers before and after the tax audit. This study uses a descriptive analysis method with a case study approach. Then the data collection consisted of secondary data obtained through documentation studies, then the data were analyzed using a paired difference test with student t. The results of a comparative analysis of the taxable income of corporate taxpayers before and after the tax office audited 20 clients of KKP Drs. A.J. Jacob & Partners Bandung, that based on the analysis of the difference test, obtained information that with a significance level below 10% or 90% confidence there is a very strong and positive relationship between sales volume, cost of goods sold, operational costs, and net income of tax objects before being examined with after inspection by the tax office. The taxable income of corporate taxpayers has a significant difference before and after. The two points above have implications for the management of KKP Drs. A.J. Jacob & Partners Bandung to continue to carry out quality bookkeeping and auditing following the tax rules for its clients so that in determining the taxable income of corporate taxpayers there are not many that must be corrected by the tax service office. As a consequence of the above differences, KKP's client, Drs. A.J. Jacob & Partners Bandung must pay the tax underpayment of Mandatory Corporate Income Tax.